Qualitative research methods - Hennink, Monique M.; Hutter, Inge, 1959-; Bailey, Ajay, 1979- (SAGE, 2011)
"The book is based on the authors' highly successful multidisciplinary qualitative methods workshops, which have been conducted for over a decade. They introduce a 'qualitative research cycle' that leads students through the selection of appropriate methods, the collection of data, and the transformation of findings into a finished project. The book provides a clear explanation of the nature of qualitative research and its key concepts"--Zadní strana obálky
Keywords: kvalitativní výzkum -- metody; sociální výzkum -- metody; qualitative research -- methods; social research -- methods; příručky; handbooks, manuals, etc